In vitro anti-ageing activities of the extracts of low-grade pineapple and lime key from Sob Prab Cooperative Limited, Lampang, Thailand / Korawinwich Boonpisuttinant ...[et.al.] - Boonpisuttinant, Korawinwich; Unkeaw, Somkit U; Chomphoo, Wirinda; Udompong, Sarinporn; Heng, Yen Khong (UiTM Press, 2022)
In this study, the low-grade pineapple and lime key from Sob Prab Cooperative Limited, Lampang, Thailand were selected to investigate the anti-ageing activities. The pineapple (PA-J) and lime key juices (LM-J) were squeezed and then the pineapple and lime key residues were extracted by maceration in 95% (v/v) ethanol (PA-E and LM-E) and boiled in distilled water (PA-W and LM-W). The extraction yields from all extracts ranged from 14.58 to 23.01, with the presence of terpenoids as a phytochemical. For anti-ageing activities of all extracts, it was found that the LM-J extract showed the highest antioxidant activity including free radical scavenging, metal chelation and lipid peroxidation activities, whereas the PA-E extract exhibited the whitening effect including tyrosinase inhibition activity and anti-melanogenesis on B16F10 cells, and the stimulation of collagen biosynthesis on human dermal fibroblasts. In addition, all extracts did not show cytotoxicity on human dermal fibroblasts at 0.1 mg mL−1.This study suggested that the PA-E and the LM extracts might be beneficial to be an active ingredient for anti-ageing cosmetics.